Estudio de la calidad proteica y del contenido de energía metabolizable del haba (vicia faba)* (1977)
In order to determínate the faba bean CEP, the possible role of bis hemaglutinine on this valué and to know the metabolizable energy in this legume we made two experiments in the poultry section of the experimental Center of Tibaitatá. In each experiment we used 45 chickens in random distribution in groups of five. In the first experiment we used diets whose proteic source was respectively isolated soybean protein (control diet), raw faba bean, and faba bean treated with steam in an autoclave. The results obtained show a low utilization of food when the ratio was prepared with faba beans, probably due to the aminoacids imbalance, also it produced hypertrophia of the páncreas due probably to the presence of antitriptyc agents which were not destroyed by the heat treatment. The nutritional valué of the faba bean protein increase 67o with the inactivation of the favine, although it is still lower (27%) compared with the control diet. In the second experiment we obtain relatively high valúes for the faba beans metabolical useful energy compared with other legume valúes like ajonjolí, which shows us that this bean is a good energy supplier.